Physical-culture and sports activity as an element of the socio-psychological re-adaptation of combat veterans - Dubrov, A.A.; Doliba, D.V.; Galkin, A.I.; Gromina, Z.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study to identify the types of physical culture and sports activity in the socio-psychological readaptation of combat veterans. Methods and structure of the study. The scientific work on the basis of the Plekhanov Russian University of Economics included the following stages: analysis of the scientific literature; questionnaire survey (n=279); interviewing of psychologists working with this target group (n=10). Results and conclusions. The empirical data showed the existence of psychological problems of the ex-combatants (through body language) and the unwillingness of many to turn to specialists for psychological help from the position of “I am strong, I will cope on my own,” as well as an active desire to take part in physical activity. Combat veterans (CV) perceive physical exercise and sports as a “normal” activity, but avoid formal psychotherapeutic programmes. The interpretation of the results points to the possibility of involving CV in the restoration of mental health through physical activity with the inclusion of special exercises for psychoregulation and the working-through of negative emotions by means of the techniques of body-oriented psychotherapy. For the successful re-adaptation and creative resocialisation of veterans, an ecosystem approach is necessary in the interdisciplinary interaction of specialists (physical-culture and sports coaches, psychologists, doctors), the raising of their qualifications, and supervision.